1992
DOI: 10.2527/1992.702588x
|View full text |Cite
|
Sign up to set email alerts
|

Forage systems for beef production from conception to slaughter: II. Stocker systems

Abstract: Fall weaned Angus calves grazed stockpiled 1) tall fescue (Festuca arundinacea Schreb.), 2) tall fescue-red clover (Trifolium pratense L.), or 3) tall fescue-alfalfa (Medicago sativa L.) or were barn-fed, 4) tall fescue hay, 5) orchardgrass (Dactylis glomerata L.)-alfalfa hay, or 6) tall fescue silage from late October to early April during each of 5 yr. Infection of the fescue with Acremonium coenophialum ranged from 0 to 55%. There were two replications each of steers and heifers for each forage system in a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
0

Year Published

1996
1996
2019
2019

Publication Types

Select...
5
2
2

Relationship

1
8

Authors

Journals

citations
Cited by 32 publications
(12 citation statements)
references
References 8 publications
0
12
0
Order By: Relevance
“…hay or silage, had lower ADG, less marbling, and were of lower quality grade than those wintered on orchardgrass (Dactylis glomerata L.)/ alfalfa (Medicago sativa L.) hay. The mean ADG during winter of steers and heifers for N-fertilized tall fescue hay or silage was 0.18 and 0.07 kg, respectively, vs. 0.50 kg for those wintered on orchardgrass-alfalfa hay (Allen et al, 1992). It is unclear if the negative impact on carcass characteristics was due to forage type, nutrient amendment, or rate of gain during winter.…”
Section: Resultsmentioning
confidence: 99%
“…hay or silage, had lower ADG, less marbling, and were of lower quality grade than those wintered on orchardgrass (Dactylis glomerata L.)/ alfalfa (Medicago sativa L.) hay. The mean ADG during winter of steers and heifers for N-fertilized tall fescue hay or silage was 0.18 and 0.07 kg, respectively, vs. 0.50 kg for those wintered on orchardgrass-alfalfa hay (Allen et al, 1992). It is unclear if the negative impact on carcass characteristics was due to forage type, nutrient amendment, or rate of gain during winter.…”
Section: Resultsmentioning
confidence: 99%
“…Allen et al [10] reported that body weight gains of calves grazing stockpiled pastures of alfalfa-tall fescue were greater than those grazing red clover-tall fescue or N-fertilized tall fescue. Ladino clover in endophyte-infected tall fescue also resulted in better average animal gains than red clover or Korean lespedeza [11].…”
Section: Introductionmentioning
confidence: 99%
“…Nitrogen‐fertilized tall fescue and tall fescue‐red clover were stockpiled each year beginning in early August immediately following the final summer grazing (0.8‐inch sward height). Stockpiling tall fescue‐alfalfa was delayed until early September because previous results showed that earlier stockpiling allowed alfalfa to become over‐mature before grazing began (1,3). Yearling Angus steers and heifers (average initial weight 550 lb) began grazing stockpiled forages in early November (stocking rate = one yearling per 0.67 acre).…”
Section: Long‐term Grazing Studymentioning
confidence: 99%